Culturally adapting an evidence-based intervention to promote a healthy diet and lifestyle for Yup'ik Alaska native communities. Issue 1 (31st December 2023) - Hopkins, Scarlett E.; Orr, Eliza; Boyer, Bert B.; Thompson, Beti
ABSTRACT: Underserved populations are at increased risk for obesity and related cardiovascular disease, type 2 diabetes, and other chronic diseases. Lack of access to healthy foods, sedentary behaviour, and other social environmental factors contribute to disease risk. Yup'ik Alaska Native communities are experiencing lifestyle changes that are likely to affect their cardiometabolic risks. Barrera & Castro's Cultural Adaptation Framework was used to adapt an evidence-based intervention (EBI) originally designed for Latino communities for use in Yup'ik communities. Focus groups and key informant interviews were held in two Yup'ik communities. Major themes included causes of obesity, barriers and facilitators to healthy foods and physical activity, and intervention ideas. The adaptation process was guided by a Community Planning Group of Yup'ik women and included information gathering, preliminary adaptation design, preliminary adaptation tests, and adaptation refinement. Two of the adapted educational modules were pilot tested. Involving community members as co-researchers in cultural adaptation is vital for an EBI to be effective in another population. Small group gatherings led by local lay health workers are culturally appropriate and may be an effective health promotion model in Yup'ik communities. Social environmental factors affecting healthy food availability and physical activity need further exploration.